What is the solution to the equation? -7(x - 4) + 8x = 12 + 14 x= I got 7

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

What is the solution to the equation? -7(x - 4) + 8x = 12 + 14 x= I got 7

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

I think I'm wrong
One second let me solve it :)
ok :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

No
Simplifying -7(x + -4) + 8x = 12 + 14 Reorder the terms: -7(-4 + x) + 8x = 12 + 14 (-4 * -7 + x * -7) + 8x = 12 + 14 (28 + -7x) + 8x = 12 + 14 Combine like terms: -7x + 8x = 1x 28 + 1x = 12 + 14 Combine like terms: 12 + 14 = 26 28 + 1x = 26 Solving 28 + 1x = 26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + 1x = 26 + -28 Combine like terms: 28 + -28 = 0 0 + 1x = 26 + -28 1x = 26 + -28 Combine like terms: 26 + -28 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2 is ur answer
Thank You @Agl202
Anytime! =D

Not the answer you are looking for?

Search for more explanations.

Ask your own question